Transformation of Settlement caused by Housing Development in Suburbs of Semarang - Muladica, Nur; Murtini, Titien Woro; Suprapti, Atiek (Jurnal Teknik Sipil dan Perencanaan, 2018)
Abstract. The development of the region towards the outskirts of the city has become a common phenomenon of cities in Indonesia. The area that was formerly a deserted area is now a sought-after area of urban society. This is due to limited land in the city center causing the start of the spread of occupancy in the suburbs. The development of suburban areas that will undergo a transition causes a change of space in the region This phenomenon can be found in the city of Semarang. One of them is the district of Mijen Semarang. The area that was formerly a small settlement with the potential of rubber forest farming has changed into one of the elite areas in the city of Semarang. The emergence of housing Bukit Semarang Baru (BSB) as a catalyst has a great impact on the development of the surrounding environment. Bukit Semarang Baru (BSB) in Mijen District, Semarang City is a new city concept housing that provides housing, education, industry, recreation and other commercial facilities. The transfer of land from rubber plantation to BSB housing is estimated to cause the transformation of space related to the function and land use in the surrounding settlements, especially the area directly adjacent to the village of Wonolopo. This research uses a rationalistic approach with qualitative paradigm, which in this study aims to understand and know the pattern of settlement transformation in settlements that occur in the village Wonolopo, Mijen, Semarang. Through this research is expected to be able to analyze and know how big the change of settlement space